The Impact of The Indonesian Ulema Council’s Fatwa on Stock Performance Using the Causal Impact Method: Empirical Evidence From Suspected Pro-Israel Firms - Thalia Dinda Millenia Putri; Rofikoh Rokhim (Eduvest - Journal of Universal Studies, 2025)
The Israel-Palestine conflict has long influenced geopolitical and economic spheres globally, affecting sectors including religious organizations. In Indonesia, the Indonesian Ulema Council (MUI) issued Fatwa No. 83 in November 2023, calling for a boycott of companies perceived as supporting Israel. This fatwa is expected to impact the stock performance of associated companies, especially in sectors sensitive to public sentiment, such as retail and fast food. Although religious announcements are known to affect consumer behavior and financial markets, limited research exists on the impact of religious interventions, like fatwas, on Indonesia’s capital markets (Alshammari & Ory, 2023; Li & Cai, 2016). This study examines the impact of MUI’s fatwa on the stock performance of three Indonesian companies—PT Mitra Adiperkasa Tbk. (MAPI), PT Fast Food Indonesia Tbk. (FAST), and PT Unilever Indonesia Tbk. (UNVR)—with alleged ties to Israel. By assessing post-fatwa stock price changes, it aims to reveal how religiously motivated socio-political actions influence investor sentiment and market behavior in Indonesia’s emerging market. Utilizing the Bayesian Structural Time-Series (BSTS) model within the Causal Impact framework, this study analyzes daily stock price data over six months pre-fatwa (from May 8, 2023) and three post-fatwa intervals: 7 days (November 15, 2023), 14 days (November 22, 2023), and 30 days (December 8, 2023) after the fatwa. The Indonesia Composite Index (IHSG) serves as a covariate to distinguish the fatwa’s specific impact from general market trends.